Ewolucja i współkształtowanie – zasada wzajemnej stymulacji między krytykami a artystami w Galerii Foksal (Programy Galerii w latach 1966–1981) - Dzierżyc-Horniak, Anna (Acta Universitatis Nicolai Copernici Zabytkoznawstwo i Konserwatorstwo, 2011)
One of the sources of “success” of the Foksal Gallery was beyond any doubt the functioning formula based on cooperation of artists and critics, who ran the critics’ gallery. This process can be apparently seen in the program manifests from 1966–1981, which fulfillment were the artistic activities led in and outside the Gallery. The mentioned cooperation was formed on the experience from the terrains of Lublin – the “Zamek” Group and the “Struktury” magazine (the second half of the 50’s), and Warsaw – apprenticeship at M. Bogusz in his Krzywe Koło Gallery (the beginning of the 60’s). Critics like W. Borowski, A. Ptaszkowska, M. Tchorek, focused later on such artists like T. Kantor and H. Stażewski, were able to start implementing their project of a gallery. In the text Introduction to a general theory of Place (1966) they declared that the gallery will be given to an artist, so it could become his own workshop, an open space. Exhibitions, such as environment checked in those postulates. In 1968, another manifest was formed – What we do not like about the Foksal PSP Gallery, which was immediately answered by the artists. Winter Assemblage (1969) was planned as a series of actions without any clear beginning and end. In the same year, after the actions taken on the Złote Grono symposium in Zielona Góra, in the New Regulations of Foksal PSP Gallery, there was a suggestion of transforming this institution into a type of information point, which was suppose to accept incoming information without any selection. However, the project led to a conf lict and Foksal collapsed. In 1970 on an Art Symposium Wrocław ’70, A. Turowski – who joined the Gallery at that time – presented the Centre of Artistic Searches project. The Centre was formed to “serve the artist and their work” in a modern way, by popularizing and documenting it, and simultaneously deter mining experimental searches. In subsequent theoretical propositions – Living Archive and Documentation (1971) – the authors postulated accepting a strategy defining the work of art in a moment, in which it was “neutrally present” and at the same time they were objecting to the domination of the documentation on artistic fact. The soon organized shows became the unmasking of the ways the institution worked – prolonged the lasting of an impermanent work of art, which were the new forms of artistic utterances. After 1981 the program activity of the Gallery was in a considerable degree limited.